Analysis of the Health Assessment Level of Cooperatives in View of NPL and Investment Levels in the MSME Sector during the Covid-19 Pandemic (Case Study of the Berkah Savings and Loans Cooperative in Makassar City) - Nahriana, Nahriana (Cita konsultindo, 2024)
Micro, Small and Medium Enterprises or Abbreviated as MSMEs is one of the many sectors that are very important for the development of the national economy. The cooperative’s healts level can be calculated using one of the formulas, namely Non-Performing Loans or NPL. The assessment of the health of cooperatives can also be seen from the increase or decrease in investment by MSME actors. This study aims to determine how the level of cooperative health assessment reviewed in NPL and the level of investment in the MSME sector. This study uses a qualitative descriptive method and uses the NPL formula. The sample of this research is the KSP Berkat on Jl. Tamalate 5 Makassar city. The data in this study were obtained from the result of interview at KSP Berkat in 2020-2021. The results of this study describe the cooperative’s health level, which is 4,75% or is in the healthy category.